2006
DOI: 10.1017/s0022215106000223
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of complementary therapy use in patients undergoing vestibular assessment

Abstract: Sixteen per cent of patients seen for vestibular assessment had tried some form of complementary therapy for their vestibular symptoms. Clinicians should be aware of this and of the potential interactions between complementary therapies and conventional medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In the UK, a review of large scale surveys indicated a mean one year prevalence of complementary and alternative medicine uptake in adults of 39.9 per cent (range, 10–100 per cent), and a mean lifetime prevalence of 58.7 per cent (range, 44–71 per cent) 4 . The use of complementary and alternative medicine in patients with audiovestibular symptoms and disorders has been noted, specifically in cases of imbalance, 5 tinnitus 6 , 7 and hearing loss, 8 although to the authors’ knowledge there is no randomised controlled trial evidence to support any specific therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, a review of large scale surveys indicated a mean one year prevalence of complementary and alternative medicine uptake in adults of 39.9 per cent (range, 10–100 per cent), and a mean lifetime prevalence of 58.7 per cent (range, 44–71 per cent) 4 . The use of complementary and alternative medicine in patients with audiovestibular symptoms and disorders has been noted, specifically in cases of imbalance, 5 tinnitus 6 , 7 and hearing loss, 8 although to the authors’ knowledge there is no randomised controlled trial evidence to support any specific therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Complementary, alternative and traditional therapies are becoming ever more popular, being used by 33 to 42 per cent of the general US population 1 . Commonly utilised therapies include acupuncture, homeopathy and herbal medicine 2 . The major areas of Arab traditional therapy are herbal, kaiy and cupping 3 .…”
Section: Introductionmentioning
confidence: 99%